Pengembangan Media Papanca “Papan Panca Indera” pada Pembelajaran Bahasa Indonesia Keterampilan Berbicara Siswa Kelas 1 Sekolah Dasar - Chandra, Milke Audina; Poerwanti, Endang; Mukhlishina, Innany (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
Media is a tool that teachers use to convey material during the learning process. Therefore, media is very important to use during the learning process. The aim of this research is to produce the PAPANCA media product 'Papan Panca Indra' which is suitable for use to improve the speaking skills of grade 1 elementary school students. The type of research used is development research or Research and Development (R&D). The method used is experimental. The research model used is the Addie model from Dick and Carey. The data collection techniques used were observation and interviews. The results of material expert validation and media expert validation stated that the PAPANCA media 'Papan Panca Indra' was suitable for use and did not need further revision. The value obtained from material expert validation was 80% and from media expert validation a value of 80% was obtained. The PAPANCA media 'Papan Panca Senses' was declared very worthy by getting the very good category to be used and implemented to improve speaking skills in the Indonesian language subject chapter 1